Precarity and the pandemic: COVID-19 and poverty incidence, intensity, and severity in developing countries - Andrew Sumner; Eduardo Ortiz-Juarez; Chris Hoy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper makes a set of estimates for the potential impact of the COVID-19 pandemic on poverty incidence, intensity, and severity in developing countries and on the distribution of global poverty. We conclude there could be increases in poverty of a substantial magnitude-up to 400 million new poor living under the 1.90 poverty line, over 500 million new poor living under the poverty lines of 3.20 and 5.50. Further, the global income shortfall below each poverty line could expand by up to 60 per cent; the daily income losses could amount to 350m among those living under 1.90 per day and almost 200 million among the group of people newly pushed into extreme poverty. Finally, we present country-level poverty estimates that show the location of global poverty is likely to shift towards middle-income countries and South Asia and East Asia. Our estimates are indication of the range of potential outcomes. If anything, our estimates show the extent of precarity in developing countries and the fragility of much poverty reduction to any economic shock.
Keywords: I32; 330; COVID-19; crisis; global poverty; precarity; SDGs; vulnerability